COVID-19 and food security in Ethiopia: Do social protection programs protect? - Abay, Kibrom A.; Berhane, Guush; Hoddinott, John F.; Tafere, Kibrom (International Food Policy Research Institute, 2020)
We assess the impact of Ethiopia’s flagship social protection program, the Productive Safety Net Program (PSNP) on the adverse impacts of the COVID-19 pandemic on food and nutrition security of households, mothers, and children. We use both pre-pandemic in-person household survey data and a post-pandemic phone survey. Two thirds of our respondents reported that their incomes had fallen after the pandemic began and almost half reported that their ability to satisfy their food needs had worsened. Employing a household fixed effects difference-in-difference approach, we find that the household food insecurity increased by 11.7 percentage points and the size of the food gap by 0.47 months in the aftermath of the onset of the pandemic. Participation in the PSNP offsets virtually all of this adverse change; the likelihood of becoming food insecure increased by only 2.4 percentage points for PSNP households and the duration of the food gap increased by only 0.13 months. The protective role of PSNP is greater for poorer households and those living in remote areas. Results are robust to definitions of PSNP participation, different estimators and how we account for the non-randomness of mobile phone ownership. PSNP households were less likely to reduce expenditures on health and education by 7.7 percentage points and were less likely to reduce expenditures on agricultural inputs by 13 percentage points. By contrast, mothers’ and children’s diets changed little, despite some changes in the composition of diets with consumption of animal source foods declining significantly.